Differential effects of CORM-2 and CORM-401 in murine intestinal epithelial MODE-K cells under oxidative stress - Babu, Dinesh; Leclercq, Georges; Motterlini, Roberto; Lefebvre, Romain A. (Frontiers in Pharmacology, 2017)
Carbon monoxide (CO)-releasing molecules (CO-RMs) are intensively studied to provide cytoprotective and anti-inflammatory effects of CO in inflammatory conditions including intestinal inflammation. The water-soluble CORM-A1 reduced apoptosis and NADPH oxidase (NOX)-derived reactive oxygen species (ROS) induced by tumor necrosis factor (TNF)-α/cycloheximide (CHX) in mouse MODE-K intestinal epithelial cells (IECs), without influencing TNF-α/CHX-induced mitochondrial superoxide anion (O2•). The aim of the present study in the same model was to comparatively investigate the influence of lipid-soluble CORM-2 and water-soluble CORM-401, shown in vitro to release more CO under oxidative conditions. CORM-2 abolished TNF-α/CHX-induced total cellular ROS whereas CORM-401 partially reduced it, both partially reducing TNF-α/CHX-induced cell death. Only CORM-2 increased mitochondrial O2• production after 2 h of incubation. CORM-2 reduced TNF-α/CHX-, rotenone- and antimycin-A-induced mitochondrial O2• production; CORM-401 only reduced the effect of antimycin-A. Co-treatment with CORM-401 during 1 h exposure to H2O2 reduced H2O2 (7.5 mM)-induced ROS production and cell death, whereas CORM-2 did not. The study illustrates the importance of the chemical characteristics of different CO-RMs. The lipid solubility of CORM-2 might contribute to its interference with TNF-α/CHX-induced mitochondrial ROS signaling, at least in mouse IECs. CORM-401 is more effective than other CO-RMs under H2O2-induced oxidative stress conditions.